2022
DOI: 10.1007/s00429-022-02515-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal brain dynamics of self-identity: an EEG source analysis of the current and past self

Abstract: Current research on self-identity suggests that the self is settled in a unique mental representation updated across the lifespan in autobiographical memory. Spatio-temporal brain dynamics of these cognitive processes are poorly understood. ERP studies revealed early (N170-N250) and late (P3-LPC) waveforms modulations tracking the temporal processing of global face configuration, familiarity processes, and access to autobiographical contents. Neuroimaging studies revealed that such processes encompass face-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The spatial resolution advantages of functional magnetic resonance and PET provide important brain regions for self-processing. Studies have shown that individuals induced specific early and late EEG components [ 14 , 15 ] in the process of self-recognition, and unique functional area activation [ 16 ] appeared in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution advantages of functional magnetic resonance and PET provide important brain regions for self-processing. Studies have shown that individuals induced specific early and late EEG components [ 14 , 15 ] in the process of self-recognition, and unique functional area activation [ 16 ] appeared in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%